Letters from inside a U.S. detention center: Carla's story - Juffer, Jane (Global gender, 2023)
"After fleeing homophobia and threats to her life in her native El Salvador, 'Carla' was detained for two years inside the Buffalo Federal Detention Center. Her letters provide a powerful and unique account of a queer woman's experience inside America's asylum system. Letters from Inside a US Detention Centre reconstructs Carla's story from the correspondence between Carla and Jane Juffer, a professor at Cornell University, and from excerpts from the legal decisions made while she was being held in immigration detention. Contextualised with explanation and analysis of detention in the United States, the book examines how detention exacerbates the trauma many migrants experience and becomes another site of fear, intimidation, and uncertainty. Carla's narrative is a powerful story, and one that illustrates grievous injustices in the U.S. immigration and asylum system. The book will be of immense value to immigration activists and scholars alike, especially in feminist studies, queer studies, and those studying the intersections of prisons and detention centres"--